Cohesive strength of nanocrystalline ZnO:Ga thin films deposited at room temperature - Rubio-Peña Luis (Nanoscale Research Letters, 2011)
Abstract In this study, transparent conducting nanocrystalline ZnO:Ga (GZO) films were deposited by dc magnetron sputtering at room temperature on polymers (and glass for comparison). Electrical resistivities of 8.8 × 10-4 and 2.2 × 10-3 Ω cm were obtained for films deposited on glass and polymers, respectively. The crack onset strain (COS) and the cohesive strength of the coatings were investigated by means of tensile testing. The COS is similar for different GZO coatings and occurs for nominal strains approx. 1%. The cohesive strength of coatings, which was evaluated from the initial part of the crack density evolution, was found to be between 1.3 and 1.4 GPa. For these calculations, a Young's modulus of 112 GPa was used, evaluated by nanoindentation.